Rasio Neutrofil-Limfosit (RNL) dan nilai HbA1c sebagai prediktor amputasi pada pasien kaki diabetik di RSUP Sanglah, Bali, Indonesia - Nyoman Maharmaya; Ketut Putu Yasa; I Gde Raka Widiana (DiscoverSys Inc., 2020)
Background: Amputation is a management that is needed in cases of diabetic foot but is still challenging to predict. In diabetic foot infections, there can be a disturbance in the balance of inflammatory mediators as a cause of tissue damage. Inflammation is assessed by the Neutrophil Lymphocyte Ratio (NLR), and the HbA1c value is associated with an increased risk of amputation. Wagner's classification describes the extent and weight of diabetic foot ulcers.Methods: This study is a predictive diagnostic test on diabetic foot patients who meet the inclusion criteria. Consecutive sampling was conducted from medical records of Sanglah Hospital Denpasar patients from 2017 to 2019. NLR and HbA1c records were taken from the examination before receiving the medical intervention. An analysis using a 2x2 table is used to determine sensitivity and specificity, and a ROC curve analysis to determine the cut-off point with the best sensitivity and specificity. Data were analyzed using SPSS version 20 for Windows.Results: A total of 82 patients met the inclusion criteria with an average age of 57 (46-69) years. There was 43 (52.4%) male and 39 (47.6%) females enrolled in this study. Most diabetic foot samples with Wagner III degree 35 (42.7%) and Wagner IV 34 (41.5%). A total of 31 (37.8%) patients underwent amputation. The ROC analysis showed an NLR cut-off point of 13.67 (AUC=0.617; p=0.078) with a sensitivity of 54.8% and specificity of 66.7%. ROC HbA1c analysis showed a cut-off point of 9.5% (AUC=0.455) with a sensitivity of 45.2% and specificity of 47.1%. Secondary data and operating reliability are limitations in this study, and it makes a lower sensitivity.Conclusion: The results of this study indicate that the Neutrophil-Lymphocyte Ratio (RNL) and the HbA1c value can be used as predictors of amputation in diabetic foot patients at Sanglah General Hospital, Bali, Indonesia. Latar Belakang: Amputasi merupakan penatalaksanaan yang diperlukan pada kasus kaki diabetik, namun masih sulit untuk diprediksi. Pada infeksi kaki diabetik dapat terjadi gangguan keseimbangan mediator inflamasi sebagai penyebab kerusakan jaringan. Inflamasi dinilai dari Rasio Neutrofil Limfosit (RNL) dan nilai HbA1c dihubungkan dengan meningkatnya resiko amputasi. Klasifikasi Wagner menggambarkan derajat luas dan berat ulkus kaki diabetik.Metode: Penelitian ini adalah uji diagnostik prediktif pada pasien kaki diabetik yang memenuhi kriteria inklusi. Pengambilan sampel dari rekam medis pasien RSUP Sanglah Denpasar secara konsekutif dari tahun 2017 sampai 2019. Pencatatan NLR dan HbA1c diambil dari pemeriksaan sebelum mendapatkan intervensi medis. Kemudian dilakukan analisa menggunakan tabel 2x2 untuk menentukan sensitivitas dan spesifisitas, serta analisa kurva ROC untuk menentukan cut-off point dengan sensitivitas dan spesifisitas terbaik. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Sebanyak 82 pasien memenuhi kriteria inklusi dengan rata-rata umur 57 (46-69) tahun. Terdapat 43 (52,4%) laki-laki dan 39 (47,6%) perempuan dalam penelitian ini. Sebagian besar sampel kaki diabetik dengan derajat wagner III 35 (42,7%) dan wagner IV 34 (41,5%). Sebanyak 31 (37,8%) pasien menjalani amputasi. Dari analisa ROC menunjukkan cut-off point RNL sebesar 13,67 (AUC=0,617; p=0,078) dengan sensitivitas 54,8% dan spesifisitas 66,7%. Analisa ROC HbA1c menunjukkan cut-off point sebesar 9,5% (AUC=0,455) dengan sensitivitas 45,2% dan spesifisitas 47,1%. Data sekunder dan reliabilitas operasi menjadi keterbatasan dalam penelitian ini, sehingga sensitivitasnya rendahKesimpulan: Hasil penelitian ini menunjukkan bahwa Rasio Neutrofil-Limfosit (RNL) dan nilai HbA1c dapat dipergunakan sebagai prediktor amputasi pada pasien kaki diabetik di RSUP Sanglah, Bali, Indonesia